INTERAKSI SIMBOL TORTOR NAMORA PULE DALAM UPACARA HORJA GODANG HAROAN BORU PADA MASYARAKAT ANGKOLA DI KOTA PADANGSIDIMPUAN - SHEILA ROISYAH (Universitas Negeri Medan, 2014)
This study discusses about Tortor Namora Pule in Angkola Society in Padangsidimpuan which aims to determine the structure of the presentation and interaction symbols. To examine the research purposes above, the writer uses theories related to research topics, such as the understanding of Tortor, the ceremonial sense, the theory of symbolic interaction, the structural and systems theory. This research’s been done for two months started from early December to Februari, 2015. The research location takes place in Padangsidempuan, North Sumatera.The population in this study is two people from the City Art Institute of Indigenous Padangsidimpuan, two wedding couple who performed manortor, five musicians, and one indigenous elder.The data analysis in this study uses descriptive qualitative data collection techniques which are done by observation, library research, interviews, and documentation. The results denote that the structure of Tortor Namora Pule presentation consists of several stages such as: Towards Galanggang Panortoran, Taking position, Makkobar, Manortor, Manogu, Manjalang, back to Galanggang and Mardalan. Interaction symbols contained in Tortor Namora Pule are illustrated through kinship system contained within the overall existing Tortor on Horja Godang Haroan Boru.Kinship system Dalihan Na Tolu binds between overall Tortor against Tortor Namora Pule. That attachment generates the interaction Tortor Namora Pule to the overall Tortor and spectators.Symbol interaction is also visible on the symbol of somba adat motion meaning of worship, an interaction of symbols that have meaning as a form of homage to the King Namora Pule, parents and spectators. Symbols manartar and old mangido interpreted as giving and receiving between the groom with the bride.Face to face-floor pattern on both families showed close interaction to Namora Pule. Musical accompaniment used also shows interaction to Namora pule, parents, relatives and spectators.Poem contains about the history of life, advice, hope and prayer that poured into Onang-Onang poetry, poetry is always addressed to Namora Pule. Keywords: Tortor Namora Pule, Angkola Society, Interaction Symbol.